A Study on the Climate for Creativity and Innovation : A Case Study of a 5 Star Hotel in Kuching, Sarawak / Nazaruddin Haji Hamit ... [et al.] - Haji Hamit, Nazaruddin; Abg Ahmad, Dyg Ellyn Narisa; Macop, Gabriel (Universiti Teknologi MARA Cawangan Sarawak, 2008)
Customers, in a number of industries, are constantly bombarded with run-of-themill product and business offerings. As a result, customers both desire and more often demand innovative alternatives, As in other industries, over the years, price apparently has been the determining factor in competition in the hotel industry. This however may backlash and be detrimental on the sustainability of the organization and the industry in general. The increased levels of competition for shrinking global resources combined with larger amount of complexity and change foster the emerging trends of innovating new ideas and offer newer offenngs in order to compete and stay afloat. In response, many service oriented organizations are striving to integrate novel features into their product-service offerings.